The Influence of Digital Comic Strip Media on Procedural Text Writing Skills in Elementary Schools - Mursolimah; Slamet; Roemintoyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The low skill of writing procedural texts in the Indonesian language subjects in elementary schools. Learning is needed that encourages the development of procedural text writing skills, one of which is through digital comic strip media. The purpose of this study is to analyze the effect of digital comic strip media learning on procedural text writing skills in elementary schools. The method in this study uses a quantitative approach with a one-group pretest-posttest design. The research was conducted at an elementary school in the Wonogiri district with 22 students as subjects. Data collection techniques used were observation and tests. Data analysis techniques included descriptive and inferential statistical analyses, including normality tests and paired-samples t-tests, using SPSS version 16. The results of this study indicate that using this media has a significant positive impact on students' writing skills. Students who learn using digital comic strips are more enthusiastic and motivated, and they more easily understand the structure and steps in procedural texts. Engaging visualizations and simple storylines help students connect ideas coherently and logically, so that their writing becomes more structured, complete, and creative. The implications of this research show that the use of digital comic strip media can be an effective and enjoyable learning strategy in improving elementary school students' procedural text writing skills.